El mano no gana : experiencia educativa sobre villanos y villanas de la cultura visual infantil - Monleón, Vicente (2019)
Visual Culture is present in occidental society. People who live there are influenced by images. So, it is decided to design a pedagogical innovation project that deals with the evil figures of cinema and children’s television series to criticize some of the values, gender roles and stereotypes, that are accepted by this society